Antiphospholipid Antibody Assays in 2021: Looking for a Predictive Value in Addition to a Diagnostic One - Meroni, Pier Luigi; Borghi, Maria Orietta (Frontiers in Immunology, 2021)
There is a general agreement that reporting quantitative results for some autoantibody assays may offer more diagnostic and prognostic information. Anti-phospholipid antibodies (aPL) represent the best example of a laboratory test that moved from a dichotomous to a quantitative result. For example, medium/high aPL titers are both classification and diagnostic biomarker in comparison with low titers. Moreover, higher the aPL titer and higher is the likelihood-ratio (LR) of the test. Isotype characterization was also reported to be critical since the presence of IgG is more diagnostic/prognostic than that of IgA or IgM, respectively. aPL are directed against two main autoantigens: beta2 glycoprotein I (beta2GPI) and prothrombin. However, anti-beta2GPI antibodies are more associated with the clinical spectrum of the anti-phospholipid syndrome (APS). In addition, there is evidence that antibodies recognizing domain 1 of the beta2GPI molecule display stronger diagnostic/prognostic value. This finding supports the fact that the antigen and even the epitope specificity of a given autoantibody may represent further parameters for improving its value. Besides their diagnostic meaning, aPL are also a risk factor for the clinical manifestations of the APS. In fact, the aPL titer, the IgG isotype and domain I epitope specificity are tools for better defining the risk profile of aPL positive patients. The strategy to obtain more information from aPL characterization is a lesson that can be translated to other autoantibody assays in order to improve our diagnostic and prognostic power.